Social mobilization and the Ebola virus disease in Liberia - Perry, John, 1946 February 7-; Sayndee, T. Debey, 1957- (Hamilton Books, an Imprint of Rowman & Littlefield, 2017)
The book offers a summary of the EVD crisis, and the ways it was defeated by the public who were energized by the gravity of the situation. It discusses the lessons learned, the effect of the disease on children, and the way forward for the international health care system.